Karakteristike magnetronske celice v področju UVV - Vesel, Alenka (Materiali in tehnologije, 2002)
The characteristics of a magnetron cell in the pressure range between 5.10sup-9 and 1.10sup-6 mbar were measured. The magnetron cell was made of a stainless-steel housing and a titanium cathode. The length of the cell was 35 mm and the diameter was 25 mm. A bridge electrode with a diameter of 6 mm was placed between the cathode plates. The discharge current was measured systematically at different voltages and magnetic field. It was found that in general the current at first slowly increased with increasing voltage, reached a maximum at a certain voltage and decreased rapidly with a further increase of voltage. At the pressure of 1.10sup-8 mbar, the maximum current of 0.12 muA was reached at the voltage of 6 kV and magnetic field of 0.13 T. The voltage, at which the ion current reached the maximum depended on the magnetic field density and the pressure. At low magnetic field the peak current was obtained at relatively low voltage. The same applied for the pressure. In any case the discharge expressed good stability in a wide range of pressure between 5.10sup-9 and 1.10sup-6 mbar, voltage between 1 and 8 kV and magnetic field density between 0.1 and 0.2 T.
Keywords: magnetronska celica; električne lastnosti; visoki vakuum